Chapter Рецепция ренессансной поэмы Песня о зубре Николая Гусовского в Беларуси и проблемы её перевода - Poutsileva, Larisa (Biblioteca di Studi Slavistici, 2018)
In the modern multi-linguistic concept of Belarus culture, neo-latin poetry represents an important component. The inclusion in the 1960s of the Latinist poet Nikolai Gusovskij, alongside other Renaissance poets, in Belarusian literature contributed to the growth of the national consciousness of the Russified and Sovietized Belarusians. However, the first translations of The Poem of the Bison in Belarusian and Russian, which showed clear signs of a tendentiousness aimed at adapting the text to the socio-political situation of Soviet times, remain canonical, despite the presence of new translations.